2015
DOI: 10.1016/j.ygyno.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative blood transfusion in gynecologic oncology surgery: Analysis of the National Surgical Quality Improvement Program Database

Abstract: Objective To use a large-scale multi-institutional dataset to quantify the prevalence of packed red blood cell transfusions and examine the associations between transfusion and perioperative outcomes in gynecologic cancer surgery. Methods The American College of Surgeons National Surgical Quality Improvement Program (NSQIP) participant use file was queried for all gynecologic cancer cases between 2010 and 2012. Demographic, preoperative and intraoperative variables were compared between transfusion and non-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 31 publications
(33 reference statements)
2
45
0
1
Order By: Relevance
“…Peri- and postoperative blood transfusions also have been associated with an increased risk of venous thromboembolism (VTE), higher composite morbidity, mortality, and length of hospital stay (3, 74). …”
Section: Risks Associated With Blood Transfusionmentioning
confidence: 99%
“…Peri- and postoperative blood transfusions also have been associated with an increased risk of venous thromboembolism (VTE), higher composite morbidity, mortality, and length of hospital stay (3, 74). …”
Section: Risks Associated With Blood Transfusionmentioning
confidence: 99%
“…hysterectomy), reoperation or even perioperative death. Generally, increased PBL is associated with prolonged duration of surgery, higher perioperative morbidity, delayed patient recovery, more frequent blood transfusions, and, in oncological patients, poorer long-term outcomes (1,7,(8)(9)(10)27). Perioperative blood transfusions can be associated with numerous immunological and infectious side-effects (28).…”
Section: Discussionmentioning
confidence: 99%
“…In general surgery, intraoperative transfusion of only one to two units of packed red blood cells (PRBC) has been shown to significantly elevate the risk for surgical-site infection, pneumonia, sepsis and 30-day mortality (7). In gynecological patients, blood transfusions are clearly associated with increased surgical wound infections and composite morbidity and mortality (8). Additionally, a low perioperative hemoglobin (Hb) level and blood transfusions themselves may worsen the prognosis of pelvic cancers (9,10).…”
mentioning
confidence: 99%
“…The Gynecologic Oncology Restrictive Transfusion Protocol was implemented by our department based on multiple studies showing the preponderance of evidence highlighting the safety and feasibility of a restrictive transfusion protocol [10][11][12]. The Gynecologic Oncology Restrictive Transfusion Protocol required that no blood transfusions would be administered postoperatively for hemoglobin greater than 7.0 g/dL (or hematocrit greater than 21.0%) and that all packed red blood cells were administered in one unit increments followed by reevaluation of blood parameters [11].…”
Section: Methodsmentioning
confidence: 99%
“…When assessing the use of restrictive transfusion practices among a gynecologic oncology patient population, investigations conducted by Boone et al demonstrated that a restrictive transfusion protocol did not result in increased morbidity or mortality [11]. An additional study in 2015 analyzing National Surgical Quality Improvement Program data for all gynecologic cancer cases reported on composite morbidity and mortality and suggested an association between blood transfusions and increased surgical wound infections, wound disruption, pneumonia, unplanned intubation, pulmonary embolism, ventilator use greater than 48 hours, renal failure, urinary tract infections, deep vein thrombosis, sepsis, shock and mortality, favoring creation of institutional transfusion guidelines [12].…”
Section: Introductionmentioning
confidence: 99%